Individual Differences in Dopamine Signaling in a Rodent Model of Substance Use Disorder Vulnerability - Leach, Amy (Wake Forest University, 2024)
In 2023, an estimated 48.7 million individuals in the United States experienced a substance use disorder (SUD). The ability to better identify behavioral and neurobiological markers of increased risk of developing SUD following initial drug use provides a significant opportunity to help prevent development of SUD in vulnerable populations. Forming a clearer understanding of the mechanisms that drive differences in vulnerability also enables the advancement of more effective treatments for individuals already suffering from SUD. Some behavioral traits such as sensation seeking are associated with an increased vulnerability to SUD development. However, the neurobiology underlying these traits remains unclear. Preclinical rodent models of sensation seeking demonstrate that rats that exhibit higher locomotor response to a novel environment acquire self-administration of drugs more rapidly and at lower doses compared to low responders. Multiple studies have shown correlations between locomotor response to a novel environment and mesolimbic dopamine signaling, which is integral to encoding both non-drug and drug rewards and reward-associated cues. The mechanisms that may drive differences in dopamine signaling and acquisition rates however, are not fully understood. This dissertation aimed to characterize mechanisms contributing to individual differences in dopamine release and how these differences translate to real-time dopamine signaling during reward-related behaviors. First, we used ex vivo fast-scan cyclic voltammetry (FSCV) to assess individual differences in nicotinic acetylcholine receptor (nAChR) modulation of dopamine. We revealed a previously unknown mechanism by which gamma-aminobutyric acid (GABA) signaling contributes to differential dopamine release in rats with increased locomotor response to novelty. We next examined individual differences in dopamine signaling in response to non-drug rewards and reward-associated cues and how this signaling changes across cue-reward learning. Finally, we assessed individual differences in dopamine release during cocaine self-administration from initial intake to full acquisition. Overall, this dissertation lends further support to the idea that early experience with a drug, innate traits, and the neural mechanisms underlying those traits all interact to influence vulnerability to escalated or maladaptive drug use.
Keywords: acetylcholine; cocaine; dopamine; reward; substance use disorder; vulnerability